1977
DOI: 10.1002/cpt1977222147
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of plasma albumin in relation to decreased drug binding in uremia

Abstract: The binding of sulfadiazine in the plasma of normal and uremic subjects was measured by means of an ultrafiltration technique. Patients with uremia had reduced binding of sulfadiazine due to decreased albumin-binding capacity. No conclusive evidence was found to suggest that reduced drug binding in uremia is caused by competing metabolites. Studies of purified normal and uremic albumin revealed differences in amino acid composition and variations in the protein content of the two albumin bands found on isoelec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
1
3

Year Published

1978
1978
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(29 citation statements)
references
References 4 publications
2
23
1
3
Order By: Relevance
“…Nifedipine protein binding was not modified during haemodialysis; thereby, the decrease in protein binding was probably not a competitive interaction between drug and dialysable endogenous compounds which accummulate in uraemic patients (Andreasen, 1974;Dromgoole, 1973;Sjoholm et al, 1976). This decrease could be the consequence of an alteration of plasma albumin concentration or binding capacity (Boobis, 1977); in our study, albumin concentration in normal plasma was 39 g/l, whereas in uraemic plasma, it was respectively 26 and 30 g/l before and after haemodialysis.…”
Section: Discussioncontrasting
confidence: 42%
“…Nifedipine protein binding was not modified during haemodialysis; thereby, the decrease in protein binding was probably not a competitive interaction between drug and dialysable endogenous compounds which accummulate in uraemic patients (Andreasen, 1974;Dromgoole, 1973;Sjoholm et al, 1976). This decrease could be the consequence of an alteration of plasma albumin concentration or binding capacity (Boobis, 1977); in our study, albumin concentration in normal plasma was 39 g/l, whereas in uraemic plasma, it was respectively 26 and 30 g/l before and after haemodialysis.…”
Section: Discussioncontrasting
confidence: 42%
“…warfarin site) of human serum albumin (Fehske etal., 1980 Bilirubin (mg 100ml 1) Figure 5 Free fraction values of azapropazone (0) and phenprocoumon (0) (Ghonheim & Pandya, 1975) and sulfadiazine (Boobis, 1977) while for several other drugs such correlation was apparent (Reidenberg et al, 1971;Campion, 1973;Dromgoole, 1974;O'Malley, Velasco, Pruitt & McNay, 1975;Bachmann et al, 1976;Gugler & Mueller, 1978). Several authors have suggested that the decrease in the plasma protein binding of acidic drugs in kidney disease is due to the accumulation of endogenous binding inhibitors (Craig, Evenson, Sarver & Wagnild, 1976;Sjoholm et al, 1976;OdarCederlof, 1977) which can be removed by charcoal treatment of plasma or might disappear following renal transplanation (Levy, Baliah & Procknal, 1976;Odar-Cederlof, 1977 (Fehske et al, 1980) which could explain the observed quantitative differences in the effect of disease on the binding of both drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Equation (1) assumes that the initial plasma and buffer volumes are equal prior to dialysis, that there is negligible binding of drug to the dialysis membrane, and that protein binding is linear. In cases of nonlinear plasma protein binding, equation (1) is inappropriate and will underestimate the true value for the percent free of drug in the original plasma sample.…”
Section: Calculationsmentioning
confidence: 99%
“…It has also been established that renal impairment may alter drug binding to plasma proteins (1)(2)(3)(4)(5), particularly with respect to acidic drugs (3) include hypoalbuminemia (2), the presence of irreversible and competitive inhibitors in the plasma (3,5), and altered albumin composition (1).…”
Section: Introductionmentioning
confidence: 99%